2014
DOI: 10.1007/s00431-014-2275-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a high-flow humidified nasal cannula to nasal continuous positive airway pressure in children with acute bronchiolitis: experience in a pediatric intensive care unit

Abstract: We did not find a difference between HFNC and nCPAP in the management of severe bronchiolitis in our PICU. Larger prospective studies are required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 21 publications
1
46
1
5
Order By: Relevance
“…This is in opposition to Metge et al, who found no difference with respect to RR development [17]. On the contrary, Metge et al found, in concordance with our findings, a higher FiO2 in the HFNC group, although it did not reach significance.…”
Section: Discussioncontrasting
confidence: 58%
“…This is in opposition to Metge et al, who found no difference with respect to RR development [17]. On the contrary, Metge et al found, in concordance with our findings, a higher FiO2 in the HFNC group, although it did not reach significance.…”
Section: Discussioncontrasting
confidence: 58%
“…However, leaks around the mask may cause discomfort and make it necessary to interrupt treatment. [12][13][14][15][16] A pediatric helmet has been used to deliver CPAP in neonates, infants, and preschool children with ARF. [17][18][19][20][21][22][23] In this population, CPAP by helmet was better tolerated than a facial mask, with no major complications and less need for sedation.…”
Section: Respiratory Syncytial Virus (Rsv)mentioning
confidence: 99%
“…15 In another study, data relating to 34 infants admitted to a PICU with bronchiolitis during two consecutive winters were retrospectively reviewed. 16 Nasal CPAP was used as first-line noninvasive respiratory support during the first winter and was replaced by HHHFNC (initial flow rate 1 L/kg/min, up to a maximum of 8 L/min) during the second winter. There was no statistically significant difference in physiological parameters (heart rate, respiratory rate, fraction of inspired oxygen (F i O 2 ) or partial pressure of carbon dioxide ( pCO 2 )) or length of PICU stay between the two groups.…”
Section: Role Of Hhhfnc Therapy In Bronchiolitismentioning
confidence: 99%